LOCKHART, James, The Men of Cajamarca: A Social and Biographical Study of the First Conquerors of Peru, Institute of Latín American Studies, University of Texas; University of Texas Press, Austin-London, 1972, XVI + 496 págs. - Murra, John (Histórica, 1977)
No contiene resumen